Population Pharmacokinetics of Trastuzumab Deruxtecan in Patients With HER2‐Positive Breast Cancer and Other Solid Tumors. Issue 5 (6th December 2020) - Yin, Ophelia; Xiong, Yuan; Endo, Seiko; Yoshihara, Kazutaka; Garimella, Tushar; AbuTarif, Malaz; Wada, Russ; LaCreta, Frank
Abstract : Trastuzumab deruxtecan (DS‐8201) is a human epidermal growth factor receptor 2 (HER2)–targeting antibody–drug conjugate with a novel enzyme‐cleavable linker, a topoisomerase I inhibitor payload, and a drug‐to‐antibody ratio of ≈ 8. We have characterized the population pharmacokinetics (PK) of trastuzumab deruxtecan and released drug (topoisomerase I inhibitor) in patients with HER2‐positive breast cancer or other solid tumor malignancies. This analysis includes pooled data from five clinical studies with 639 patients. Trastuzumab deruxtecan doses ranged from 0.8 to 8.0 mg/kg every 3 weeks. Serum concentrations of trastuzumab deruxtecan and released drug were analyzed using a sequential two‐step approach, with the nonlinear mixed‐effects modeling methods. Covariate assessment was based upon stepwise forward‐addition and backward‐elimination process, followed by both univariate and multivariate analysis quantifying their impact on steady‐state exposure of trastuzumab deruxtecan and released drug. A two‐compartment model with linear elimination best described PK profiles of intact trastuzumab deruxtecan, while a one‐compartment model with time‐varying release‐rate constant and linear elimination described released‐drug PK profiles. Statistically significant covariates (country, tumor size, sex, formulation, age, body weight, albumin, total bilirubin, and aspartate aminotransferase) resulted in < 20% change in steady‐state area under the concentration‐time curve of trastuzumab deruxtecan and released drug, except for increased body weight (95th percentile, 86 kg) and decreased albumin (5th percentile, 31 g/L). Analysis of patients stratified by country, race, renal function, and hepatic function found no clinically meaningful differences in steady‐state exposure of intact trastuzumab deruxtecan or released drug. Overall, results suggest that no dose adjustment based on tested covariates or in specific patient populations is warranted.